Assessing Technological Pedagogical Content Knowledge (TPACK) and Teaching Effectiveness of Senior High School Teachers: An Input for Teacher Development Plan - Adelita D. Castillo; Karen A. Manaig; Alberto D. Yazon (Research Synergy Foundation, 2024)
This study investigates the Technology-Enhanced Pedagogical Skills and Technological Pedagogical Content Knowledge (TPACK) levels among senior high school teachers in Biñan City, highlighting the importance of integrating technology effectively in education. Technology-Enhanced Pedagogical Skills are crucial for enhancing learning outcomes through the appropriate use of technology in teaching specific subjects. The study involved 54 teachers from seven schools who were selected based on their proficiency in digital tools. Using a survey questionnaire, the research assessed teachers’ TPACK competency, socio-demographic backgrounds, and perceived teaching effectiveness. The findings aim to determine the correlation between TPACK levels and teaching effectiveness and provide insights for educational policies and professional development programs to enhance technology integration in teaching practices, ultimately improving student learning experiences and outcomes.